ORGANIZATIONAL CLIMATE FOR WORK MOTIVATION STIMULATION IN REGIONAL FINANCIAL AGENCY - Yantu, Irwan (Universitas Brawijaya, Indonesia, 2018)
This study aims to examine and analyze the effect of organizational climate on work motivation on government employees at Gorontalo Regional Finance Agency. The population and samples used in this study were 86 people taken at random and then the data obtained from the sample were analyzed by using simple regression analysis technique. The results of the analysis show that the organizational climate does not affect the work motivation of civil servants. Of the many factors that can influence work motivation, the organizational climate has no contribution to that influence.